Prevalence of hepatitis B surface antigen (HBsAg) in a blood donor population born prior to and after implementation of universal HBV vaccination in Shenzhen, China. Issue 1 (December 2016) - Wang, Zhen; Zeng, Jinfeng; Li, Tingting; Zheng, Xin; Xu, Xiaoxuan; Ye, Xianlin; Lu, Liang; Zhu, Weigang; Yang, Baocheng; Allain, Jean-Pierre; Li, Chengyao
Abstract Background Neonatal hepatitis B vaccination program at birth has been implemented nationwide since 1992 in China. However, current HBV prevalence status in blood donors has not been entirely examined, which may impact HBV safety in blood donations as the vaccinees over 18 years old progressively become the majority population of blood donors. Methods In this study, 569, 145 blood donors were screened for HBsAg by rapid tests and enzyme immunoassays, among them 475, 538 blood samples with negative HBsAg were further screened for HBV DNA by nucleic acid testing between 2005 and 2014 at Shenzhen blood center. Results An overall 2.3 % HBsAg prevalence was found in the blood donor population during the past 10 years (2.86 % in 2005, 1.76 % in 2010, and 2.79 % in 2014, respectively). HBsAg seroconversion occurred in 0.37 % of repeat-donors. When stratified by age, the prevalence of HBsAg was found significantly higher in younger donors age 18–25 years (2.73 %) than in those 26–35 years (2.13 %), 36–45 years (2.03 %) and 46–58 years (1.71 %) (P  < 0.001), unexpectedly suggesting that younger donors remained at risk of chronic HBV infection. Assuming that donors aged 18–22 born before or after 1992 were non-vaccinated and vaccinated, respectively, HBsAg prevalence was higher in first-time donors born ≥1992 (3.9 %) than prior to 1992 (3.5 %, P  = 0.005). The incidence of HBV infection in the 5-year period examined was significantly lower in repeat-donors born ≥1992 (0.27 %) than prior to 1992 (0.6 %, P  = 0.008). The yield of HBV DNA+/HBsAg- donors was 1:3, 302, including 1:4, 486 occult infections and 1:43, 231 window period infections. Conclusion Young blood donors born after implementation of universal HBV vaccination in China presented higher prevalence of HBsAg but lower incidence of HBsAg seroconversion than older, presumed unvaccinated, donors. HBV vaccine boosting for adolescents at 15–17 years old prior to reaching blood donor age might help improve blood safety.